THE UTILITY OF SCORES IN DIFFERENTIATING STEATOSIS, STEATOHEPATITIS, AND FIBROSIS...International Congress For Students, Young Doctors And Pharmacists Marisiensis, May 22-26, 2024, Targu Mures, Romania. - Trocin, Cristina; Tagadiuc, Olga (Acta Marisiensis. Seria Medica)
Background: Steatotic liver disease is one of the most common hepatic disorder, which poses a significant economic and health burden worldwide. It can manifest through a wide spectrum of disorders, from steatosis to steatohepatitis, fibrosis, cirrhosis, and ultimately hepatocellular carcinoma. Accurately quantifying the presence and severity of liver disease holds paramount importance in devising therapeutic approaches, prognosis, and stratifying the potential complication risks. Objective: The aim of this study was to investigate the effectiveness of widely available biomarker-based scores in identifying liver-related pathological conditions and their stages. Material and methods: A narrative review was carried out following an extensive search of scientific articles in English with reference to clinical trials published between 2009 and 2024 in major scientific databases, in particular: PubMed, Mayo Clinic Laboratories and Cochrane. Among the 356 articles studied, only 142 were chosen for inclusion in the study. Results : The phenomenon of hepatic steatosis has shown a vertiginous increase in recent years, where the evolutionary cascade from steatosis to steatohepatitis, fibrosis, and cirrhosis takes more complex diagnostic forms, while the use of invasive tests involves additional risks. Although liver biopsy remains the gold standard for definitive diagnosis and staging of chronic liver disease, it is not the most accessible and suitable, due to its significant resource requirement, inherent invasiveness, and susceptibility to sampling error. In this context, the use of hepatic scores based on serological biomarkers constitutes an alternative, promoted as instruments to address the challenge of early risk stratification in hepatic disease, predict liver-related outcomes, and guide therapeutic interventions. The FibroTest, ActiTest, and SteatoTest have been patented as 'in vitro diagnostic multivariate index assays' designed for the assessment of fibrosis and steatosis grades. These assays are accessible online and incorporate clinical security algorithms adjusted for age and gender. It is noteworthy that these scores exhibit varying performance characteristics across different liver disease contexts, decreasing the necessity for invasive investigations, being rapid to perform and analyze, cost-effective, and reproducible. They also distinctly differentiate between various entities in liver pathology, such as inflammation and fibrosis, while remaining unaffected by impairment in liver function. Furthermore, they possess the capability to predict both progression and regression of liver conditions. Conclusions: Noninvasive scores are easy and nonexpensive tools to screen for steatosis, steatohepatitis and advanced fibrosis. Furthermore, these scores can be applied across a broad spectrum of patients, facilitating early diagnosis and reducing the incidence of patients identified in advanced stages of the disease.